1992
DOI: 10.1007/bf03008338
|View full text |Cite
|
Sign up to set email alerts
|

Epidural morphine reduces halothane MAC in humans

Abstract: Systemic administration of opiates reduces the minimum alveolar concentration (MAC) of volatile anaesthetics in animals and humans. 1-3 Intrathecal administration of morphine has been shown to reduce isoflurane MAC in the rat 4 and halothane MAC in humans. 5 Recently, however, in a randomized double-blind study, Licina et al. 6 were unable to confirm these results and observed that intrathecal morphine did not reduce halothane MAC in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It has been reported that intravenous or intrathecal morphine is able to reduce the minimum alveolar concentration of halothane [8][9][10] . In the present study, the fact that naloxone blocked the sevoflurane-induced inhibition of nociceptive C responses provides further support for the involvement of spinal opioid receptors in antinociception mediated by sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that intravenous or intrathecal morphine is able to reduce the minimum alveolar concentration of halothane [8][9][10] . In the present study, the fact that naloxone blocked the sevoflurane-induced inhibition of nociceptive C responses provides further support for the involvement of spinal opioid receptors in antinociception mediated by sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a common property of a wide spectrum of general anesthetics, including barbiturates and propofol, is enhancement of the action of GABA A receptors [1][2][3][4] . Increasing evidence have indicated that the spinal cord is pivotal in the immobility induced by volatile anesthetics because the anesthetics depress the activity of α-motoneurons in the spinal cord [5,6] , in which process spinal GABA receptors and opioid peptide receptors may be involved [7][8][9][10] . However, there has been few study on the effects of sevoflurane on pain processing in the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…For example, epidural morphine reduced halothane MAC by at least 33% in dogs (Valverde et al 1989) and 14% in ponies (Doherty et al 1997). In humans, it is reported that epidural morphine reduces the halothane MAC by 28% (Schwieger et al 1992) and isoflurane MAC by 14% (Kashyap et al 2003). However, neither epidural morphine nor buprenorphine MAC sparing effects have been described in pigs according to the cited references.…”
mentioning
confidence: 99%
“…[5] Epidural morphine reduces the MAC of halothane by 28% and isoflurane by 14%. [10,11] Strum et al had supplemented general anaesthesia with epidural analgesia for open surgical procedures in morbidly obese patients. [6] But he administered age adjusted 1 MAC end-tidal concentrations of inhalational agents (desflurane/sevoflurane) and did not account for the MAC sparing effect of epidural local anaesthetics and opioids.…”
Section: Discussionmentioning
confidence: 99%